Feasibility Analysis and Simulation of a Stand-Alone Photovoltaic Energy System for Electricity Generation and Environmental Sustainability – Equivalent to 650VA Fuel-Powered Generator – Popularly Known as “I Pass My Neighbour” - Ani, Vincent Anayochukwu (Frontiers in Energy Research, 2015)
Photovoltaic (PV) power system can be used to replace wholly 650VA generator for electricity generation for household use in Nigeria. This paper presented the feasibility analysis of load data and simulation study of a stand-alone PV power system that produced the electrical needs of a household. This study is based on designing of PV energy system for household use. The patterns of load consumption within the household were studied and suitably modeled for simulation. The simulation study indicates that energy requirements to provide electricity which is equivalent to 650VA generator for household use in Nigeria can be accomplished by 520W solar PV array, 2312 Ah nominal capacity battery, and a 1kW DC/AC inverter. This would be suitable for deployment of 100% clean energy for environmental sustainability and uninterruptable power performance in the household. The results of this research show that, with a low-power consuming appliances, it is possible to meet the entire annual electricity demand of a single household solely through a stand-alone PV energy supply. Installing solar panels by most Nigerian home can significantly reduce home reliance on government power thereby reduce the strain on the current capacity of our power generation infrastructure. A detailed design and description of the system were presented in this paper.